Implementation of proven interventions in general medical inpatients: development and evaluation of a new quality indicator for drug therapy. Issue 4 (4th August 2008) - Huang, C; Loewen, P; Pelletier, T; Slater, J; Chung, M
Abstract : Background: Among adult general medical inpatients, there are numerous interventions whose benefits outweigh their risks. However, there are no published reports describing the overall use of such proven interventions in this population. Objectives: To determine implementation rates of a broad range of interventions while accounting for valid reasons for non-use, predictors of implementation and feasibility of generating new indices to describe quality of care. Methods: Based on a review of current practice guidelines and clinical trials related to five common conditions, implementation rates of 17 interventions were assessed retrospectively. Subjects were a complete sample of 150 adults with target medical conditions discharged from general medical units at an urban community hospital. Results: The Ideal Intervention Index (3I), which described the proportion of ideal intervention opportunities that were implemented, was 0.74 (95% CI 0.70 to 0.78). The Justified Non-Use Index (JNUI), which described the proportion of all the interventions not implemented that were justified by a valid reason for non-use, was 0.49 (95% CI 0.41 to 0.55). Smoking cessation therapy in high-risk patients had the lowest indices (3I 0.30, 95% CI 0.00 to 0.60; JNUI 0.00), and aspirin for secondary stroke prevention had the highest (3I 1.0; JNUI 1.0). Conclusions: Overall, proven interventions are underused among the patients studied, and the reasons for non-use are frequently not readily discernible. There is potential for improvement, but research is required to further investigate reasons for non-use. It is feasible to measure implementation rates of proven interventions as an indicator of quality of care using the indices developed.